Processual Deadlines and Their Application Issues - Akbarova Bibikhon Adkhamovna (Scholar Express Journals, 2022)
The terms of deadline used in civil-legal relations are appointed on the grounds established by civil legislation. Processual actions are carried out within the time limits established by law. In this article highlights of term deadline and issues of processual deadline in the national law in Uzbekistan
Keywords: Deadline; Processual Deadline; Civil Legislation; Issues Of Processual Deadline